High‐Performance Directional Water Transport Using a Two‐Dimensional Periodic Janus Gradient Structure (Small Methods 12/2022). Issue 12 (13th December 2022) - Xie, Dongdong; Zhang, Bao Yue; Wang, Guilian; Sun, Yunna; Wu, Chaofeng; Ding, Guifu
Abstract : Inside Front Cover In article number 2200812, being inspired by the superiorities of several biont characters, Ding and co‐workers created an innovative two‐dimensional functional surface with periodic Janus gradient structures and demonstrated a long‐range and ultrafast directional water transport with an ultralow volume loss. This provides an insightful pathway in realizing high‐performance water manipulation and possibly facilitates innovative applications in multidisciplinary fields.